Evaluation of Hepatic Detoxification Effects of Enteromorpha prolifera Polysaccharides against Aflatoxin B1 in Broiler Chickens - Wen-Chao Liu; Yu-Ying Yang; Karthika Pushparaj; Balamuralikrishnan Balasubramanian (MDPI AG, 2022)
Aflatoxin B1 (AFB1) is a major risk factor in animal feed. Seaweed (Enteromorpha prolifera)-derived polysaccharides (SDP) are natural antioxidants with multiple biological functions, which may have an in vivo detoxification effect on AFB1. The current study aimed to evaluate whether SDP could mitigate AFB1-induced hepatotoxicity in broilers. A total of 216 chickens (male, 5 weeks old) were randomly allocated to three groups with differing feeding patterns, lasting 4 weeks: (1) control group (CON, fed a basal diet); (2) AFB1 group (fed a basal diet mixed with 0.1 mg/kg AFB1); and (3) AFB1 + SDP group (AFB1 group + 0.25% SDP). The results showed that dietary SDP improved the liver function-related biochemical indicators in serum, and reversed the increase in relative liver weight, hepatic apoptosis and histological damage of broilers exposed to AFB1. SDP treatment also reduced the activity and mRNA expression of phase I detoxification enzymes, while increasing the activity and mRNA expression of phase II detoxification enzymes in the livers of AFB1-exposed broilers, which was involved in the activation of p38 mitogen-activated protein kinase (p38MAPK)/nuclear factor erythroid 2-related factor 2 (Nrf2) signaling. In conclusion, dietary SDP alleviated AFB1-induced liver injury of broilers through inhibiting phase I detoxification enzymes and upregulating p38MAPK/Nrf2-mediated phase II detoxification enzymes pathway.